Pulmonary Hypertension in Adult Congenital Heart Disease: From Registry to Policy - Lucia Kris Dinarti (ACI (Acta Cardiologia Indonesiana), 2017)
Pulmonary Hypertension in Adult Congenital Heart Disease: From Registry to Policy